ANALISIS STRATEGI INOVASI PADA PT PENGELOLAAN BIAYA PARKIR UNTUK MENGATASI PARKIR ILEGAL UNTUK MENINGKATKAN PENDAPATAN UMKM DI KOTA BATAM - Haldy, Muhammad; Khoiri, M; Chang, Lim Weng (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
This study aims to analyze innovation strategies in parking fee management to address illegal parking issues in Batam City. The research method used is descriptive qualitative with a case study approach. Data were obtained through in-depth interviews with relevant parties, field observations, and documentation. The results indicate that implementing application-based technology for parking payments, enhancing surveillance through CCTV systems, and collaborating with the private sector are effective strategies in reducing illegal parking. Additionally, increasing public awareness through socialization and education also plays a significant role. The implementation of these strategies has successfully increased local revenue from parking fees and reduced the number of illegal parking cases in urban areas. Thus, innovation in parking fee management can be an effective solution to tackle illegal parking issues and improve public service quality in Batam City.